Experimental and simulated performance study of a small-scale gas turbine engine using Jet A-1 and palm oil biodiesel blends - Gires, Ezanee (2013)
The experimental and simulated performance of an Armfield CM4 turbojet engine was investigated for conventional Jet A-1 fuel as well as its blends with palm oil biodiesel (PME), a form of fatty acid methyl ester (FAME). The volumetric blends of PME with Jet A-1 are 20, 50, 70 and 100% (B20, B50, B70 and B100). Fuel heating values (FHV) of each fuel mixture were obtained by calometric analysis and were used to estimate changes in CM4 performance which were verified experimentally. The experimental tests included performance tests for Jet A-1 and B20, while the performances of B50 to B100 were simulated using GasTurb 11 analytical software after verification of simulated and experimental results for Jet A-1 and B20. Values of thrust, fuel flow, temperature and pressure distribution along the engine and engine speed were available from experimental measurements, whereas other values of merit were calculated using parametric cycle analysis and one-dimensional flow assumptions. In terms of maximum measured thrust, Jet A-1 yielded the highest value of 216 N, decreasing by 0.77%, 4%, 8% and 12% with B20, B50, B70 and B100 based on experimental and simulated results. It was found that B20 produced comparable results compared to the benchmark Jet A-1 tests, particularly with thrust and thermal efficiency. Slight performance penalties occurred due to the lower energy content of the biodiesel blend. The efficiency of the combustor improved with the addition of biodiesel while the other component efficiencies remained collectively consistent. The performance parameters of the CM4 engine were found to deteriorate with increased PME content in the simulations, particularly for volumetric blends of over 50% palm oil biodiesel. This research shows that for gas turbines, PME is suitable for use as an additive to Jet A-1, but not as a complete replacement fuel.